BIORESIN: AN ALTERNATIVE MATERIAL TO RESIN FOR CONTEMPORARY NATURAL FABRIC DYEING - Utchin, Duangjai; Nakpan, Khajornsak (Journal of Social Science and Cultural, 2023)
This research article focuses on the use of resin by creating alternative material called “bioresin” to apply in natural fabric dyeing process. The bioresin that is able to coat coffee grounds is created to apply in fabric dyeing process. The purposes of this research are as follows: 1) To study resin in order to design the process of making bioresin that can coat coffee grounds by studying related documents and interview experts in resin and natural pigment. And 2) To design the process of fabric dyeing using waste coffee grounds by applying bioresin with alcohol. The result found that: 1) Resin from yang na can be used to create bioresin by using Karaya gum as emulsion and glycerin as solvent. 2) The bioresin formula 13.5 with the ratio of resin: 28 g/glycerin: 46 g/gum karaya: 26 g is the formula that is suitable for coating coffee grounds (the pH values are between 4.50 - 5.00, which is not too acidic) and it is applied in the process of dyeing muslin fibers with coffee grounds by using alcohol instead of water as in the fabric dyeing formula 7 with the ratio of bioresin: 4 g/coffee: 6 g. In addition, it is found in the process of dyeing with alcohol that after the dyeing process has been done, the raw material can be kept to reuse in fabric dyeing again. This complies with the creation that recognizes the value of reusing raw material which brings about the development of contemporary fabric dyeing process rooted from the wisdom of sustainability.